Trailing Wives and Constrained Agency Among Women Migrant Entrepreneurs: An Intersectional Perspective. (November 2021) - Lassalle, Paul; Shaw, Eleanor
This article applies an intersectional lens to analyze the lived experience of 11 women migrant entrepreneurs based in the UK. We adopt structuration as our ontology to analyze intersectionality in entrepreneurship at the interplay of macro-level structures and micro-level agency, addressing tensions between determinism and subjectivism. Findings show that women migrant entrepreneurs are trailing wives who experience constrained agency which influences their entrepreneurial activities. By highlighting the specific issues faced by entrepreneurs situated at the intersection of the oppressive structures of patriarchy and outsidership, we advance the intersectional agenda in entrepreneurship research and policymaking.